Printing on metal Inkjet transfers. - Lhotka, Bonny Pierce (Digital Art Studio Seminars, 2008)
"In this fun and instructional video, Bonny Lhotka, author of Digital Alchemy: Printmaking techniques for fine art, photography, and mixed media, shows new processes for inkjet printing on metal, metal leaf, and non-porous surfaces using custom precoats and gelatin transfers. All of the processes shown in the video can be completed with ordinary desktop and wide format printers using pigment inks. All you need is a great digital image and a little imagination to begin creating unique works of art with these one-of-a-kind printing techniques"--Resource description page.